Pengaruh Motivasi Kerja, Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada UPT Puskesmas Klenang Kidul Kabupaten Probolinggo - Arifin, Arifin; Hermanto, Hermanto; Amani, Tatik (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted on the UPT Puskesmas Klenang Kidul Probolinggo Regency with the aim of determining the influence of work motivation, work environment and organizational culture on employee performance at the UPT Puskesmas Klenang Kidul Probolinggo Regency. The type of research used is quantitative with quantitative descriptive methods. The population used in this study were all 42 employees of the UPT Puskesmas Klenang Kidul Probolinggo Regency. Sampling used a simple saturated sampling technique. The sample in this study was all 42 employees of the UPT Puskesmas Klenang Kidul, Probolinggo Regency. The data sources used in this research come from primary data and secondary data. Data was collected through questionnaires and completed through data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R2) as well as hypothesis tests (partial tests) and dominant tests. The research results show that work motivation is not significant to employee performance, the work environment is not significant to employee performance and organizational culture is significant to employee performance.